DEVELOPMENT OF BALANCE IN CHILDREN PARTICIPATING IN DIFFERENT RECREATIONAL PHYSICAL ACTIVITIES - Elpida Skaltsa; Vasiliki Kaioglou; Fotini Venetsanou (University of Ljubljana Press (Založba Univerze v Ljubljani), 2021)
Balance, an important motor coordination ability, underlies the performance of various motor skills and allows for participation in common childhood activities. Research indicates that sport participation could support balance development in children. To confirm the above effect, this study investigated whether participation in different recreational physical activities could induce differences in children's balance ability. Specifically, 138 children, 5- 11 years old (Mage=8.4±1.3), classified into four groups according to the activity they took part in (basketball, track and field, rhythmic gymnastics, contemporary dance), were assessed by the balance subset of the KörperKoordinationstest für Kinder. Pearson correlations were applied to detect associations of balance scores with age, height, body mass index (BMI) and showed significant correlations for BMI (p< .001). The analyses of covariance (covariate: BMI) that were computed on children's balance scores showed statistically significant effects of group (p< .001). Sidak post hoc tests indicated that children participating in rhythmic gymnastics surpassed all three other groups; whereas those taking part in basketball had the lowest scores in almost every balance item. It seems that the type of physical activity a child participates in could be a significant contributor to the development of his/her balance. Physical activities encompassing the execution of various balance tasks, such as rhythmic gymnastics, seem to offer children greater opportunities to make improvements in this area compared to children engaging in activities of low balancing requirements. This finding highlights the potential that is available to coaches: they can contribute to children's balance development by implementing sport-specific programs that target this human ability.